Tracking of Diversity and Evolution in the Brown Rot Fungi Monilinia fructicola, Monilinia fructigena, and Monilinia laxa - De Miccolis Angelini, Rita Milvia; Landi, Lucia; Raguseo, Celeste; Pollastro, Stefania; Faretra, Francesco; Romanazzi, Gianfranco (Frontiers in Microbiology, 2022)
Monilinia species are among the most devastating fungi worldwide as they cause brown rot and blossom blight on fruit trees. To understand the molecular bases of their pathogenic lifestyles, we compared the newly assembled genomes of single strains of Monilinia fructicola, M. fructigena and M. laxa, with those of Botrytis cinerea and Sclerotinia sclerotiorum, as the closest species within Sclerotiniaceae. Phylogenomic analysis of orthologous proteins and syntenic investigation suggest that M. laxa is closer to M. fructigena than M. fructicola, and is closest to the other investigated Sclerotiniaceae species. This indicates that M. laxa was the earliest result of the speciation process. Distinct evolutionary profiles were observed for transposable elements (TEs). M. fructicola and M. laxa showed older bursts of TE insertions, which were affected (mainly in M. fructicola) by repeat-induced point (RIP) mutation gene silencing mechanisms. These suggested frequent occurrence of the sexual process in M. fructicola. More recent TE expansion linked with low RIP action was observed in M. fructigena, with very little in S. sclerotiorum and B. cinerea. The detection of active non-syntenic TEs is indicative of horizontal gene transfer and has resulted in alterations in specific gene functions. Analysis of candidate effectors, biosynthetic gene clusters for secondary metabolites and carbohydrate-active enzymes, indicated that Monilinia genus has multiple virulence mechanisms to infect host plants, including toxins, cell-death elicitor, putative virulence factors and cell-wall-degrading enzymes. Some species-specific pathogenic factors might explain differences in terms of host plant and organ preferences between M. fructigena and the other two Monilinia species.